THE EFFECT OF THE UNDERSTANDING OF TEACHER PROFESSIONAL ALLOWANCE, JOB SATISFACTION, PROFESSIONAL COMPETENCE, PEDAGOGIC COMPETENCE AND ORGANIZATIONAL COMMITMENT TOWARDS THE POSITIVE BEHAVIOURS OF THE CERTIFIED TEACHERS - S Suhartono (Faculty of Education Universitas Negeri Malang, 2017)
This study was aimed at describing and explaining the effect of the understanding of teacher professional allowance, job satisfaction, professional competence, pedagogic competence and organizational commitment towards the positive behaviors of the certified teachers. It utilized descriptive correlational and causal-comparative research design of quantitative approach. The sample which was 274 certified teachers was taken by using proportional random sampling. The data was collected by using questionnaire and it was analyzed by using structural equation model of descriptive statistics frequency distribution. The difference test was run simultaneously by using Chow Test of regression equation test. The result of the current study showed that (1) there was influence of the teacher professional allowance understanding towards job satisfaction, professional competence, pedagogic competence and organizational commitment, (2) there was no influence of teacher professional allowance understanding towards the positives behaviors of the certified teachers, (3) there was influence of job satisfaction and organizational commitment towards the positives behaviors of the certified teachers, and (4) there was no influence of professional and pedagogic competence towards the positive behaviors of the certified teachers. Keywords: teacher professional allowance understanding, job satisfaction, professional competence, pedagogic competence, organizational commitment and the positive behavior of the certified teachers